General Consideration over the Bauhaus Material Practice: The Case of Modern Monument; Siedlung Gropius Törten Estate at Dessau, Germany (Journal of University of Babylon for Engineering Sciences, 2019)
As a remarkable case of being modern monument of Bauhaus style and social functionalist housing, Siedlung Gropius Törten Estate of Dessau needs some reassessment in architectural material study, as those are rare in todays practice. The research problem is, it is not rational to bring back the original materials again. To find out both modern facilities and original appearance in alternative choices, would be challenge as well. To introduce sustainable material practice for preset day composite conservation oriented practice accordingly, would be the research question of this study. And it should be done without any maltreatment to the originals. An investigative survey, literature review and collaboration with building and finishing material experts, were adopted as method. To cope with the specifics of Dessau, some potentials of localization and substitutions of contemporary installation were advocated after such meticulous observation. Tentative recommendations based on results, might demonstrate the possible links for further maintainable remodeling regarding the distinct architectural expression in alternative, possible preservation material practice. Such results of explicit survey will also reveal the various potentials in building and finishing material conservation technique in the future. The study will determine and establish that the Bauhaus aesthetics and its authentic value are dependent over all these materials.